Adenocarcinoma of the minor salivary gland with concurrent MAML2 and EWSR1 alterations - Sangjoon Choi; Junhun Cho; Seung Eun Lee; Chung-Hwan Baek; Yi-Kyung Kim; Hyung-Jin Kim; Young Hyeh Ko (Korean Society of Pathologists & the Korean Society for Cytopathology, 2021)
Salivary gland tumors are histologically diverse, and each entity has distinctive histopathological and molecular features. We report two cases of salivary gland tumors with unique histological and molecular findings, which have not been documented previously. The tumors were located in the base of the tongue in both patients. Most tumor cells were arranged in cords and nests, giving a trabecular-like appearance. Focally, glandular structures with intraluminal mucin and perivascular pseudorosette-like configurations were identified. Tumor cells had eosinophilic to clear cytoplasm, and showed mild nuclear atypia. They were positive for pancytokeratin and negative for S-100, p63, c-KIT, androgen receptor, and neuroendocrine markers. Multiple foci of capsular or lymphovascular invasion were identified, but the Ki-67 labeling index was low (< 5%). Fluorescence in situ hybridization revealed concurrent alterations of MAML2 and EWSR1 gene. Further investigations with a larger number of cases with similar histological and molecular features will accurately classify this tumor.